Valorisation of kraft lignin by using vanillin and lignin-based polyurethanes: Use of the biorefinery concept - Silva, Eduardo A.B. (2009)
In kraft pulp mills, the capacity of the recovery boiler is very often a limiting factor to the increase of the pulp production. Until several decades ago, an upgrade to boiler system for dealing with higher quantities of black liquor was the only alternative. The possibility of lignin extraction from black liquor seems to be much more attractive, either for energy production or combustion elsewhere, or to serve as feedstock for chemicals production. Since the beginning of the 90’s, associate Laboratory LSRE/LCM has been focused on overcoming expansion limitations in pulp industries and, in this work, we show an alternative to this industry segment for the utilization of lignin and producing high added value chemicals from renewable biomass materials. Based on the biorefinery concepts, an integrated process for producing vanillin from kraft lignin oxidation has been proposed and each of the needed unit operations has been investigated to provide a deeper scientific understanding on this subject.